Efforts to Improve Health Cadres’ Knowledge about Maternal Education Concerning Parental Feeding as a Stunting Prevention - Maya Amalia; Bhekti Imansari (Direktorat Pengabdian kepada Masyarakat Universitas Gadjah Mada, 2023)
Stunting is a condition that results from chronic malnutrition during childhood in low- and middle-income countries. The national prevalence of stunting in children under 5 years is 9 million children out of 24.5 million children. Factors that contribute to stunting include poor feeding and sanitation practices. The purpose of this community service is to provide education to health cadres in the Jaya Mekar Health Center area, West Bandung, regarding parental feeding practices as an effort to prevent stunting. The community service method is to provide education to health cadres through parental feeding booklets. This community service was carried out for 1 day, 10-10-2022, with 26 RW represented by 36 cadres in the Jaya Mekar Public Health Center area, Bandung Barat. The benefits of Community Service are expected after the cadres know about parental feeding, then it becomes a cadre education strategy for mothers (community) about how to give good food for children. The result of this education increases the knowledge of cadres significantly (0.019; 0.001) before and after providing education about parental feeding, then it becomes a cadre education strategy for mothers about how to give good food to children. Recommendations are needed for further programs to monitor cadres in providing education to mothers.